The Effectiveness of the Ittihadul Mubalighin Program in Developing the Students’ Da'wah Potential - Marwan Abdul Basit; Deiva Tazky; Yuyun Rohmatul Uyuni (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2022)
Among the programs owned by the Daarul Falah Islamic boarding school is the